Generation y and choice of mobile service provider: a study on their preference in choosing a mobile service provider at Kelantan / Nur Ilanie Ilias - Ilias, Nur Ilanie (Bachelor of Science (Hons) Statistics, 2016)
A study was conducted to identify the factors related to preference in choosing mobile service providers among the young generations’ consumers at Kelantan. A total of 126 young generations’ consumers in Kelantan who use mobile service provider were involved in the study. The significant findings include: (1) Percentage age of young generation’s consumers under the study 63% between 15 years old and 34 years old; (2) There were significant difference between consumers satisfaction with brand reputation, network experience, price/tariff plan, experience with customer service and loyalty reward. However only loyalty reward significantly influence with consumer loyalty; (3) Based on multiple regression model , the researcher may highlight the attribute of brand reputation, network experience, price/tariff plan, experience with customer service and loyalty reward as the factors that affecting the young generation will be satisfy’ user since there has significant relationship with consumer satisfaction